Instrumen Asesmen Psikomotorik Pembelajaran Bahasa Arab - R Saleh, Sriwahyuningsih; Husain, Dahlia; M.S Lagalo, Anggraeni (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Characteristics of psychomotor skills in the form of sensory skills, alertness, and the ability to act in a complex manner. Psychomotor skills of students in learning Arabic can be seen in the skills of students in carrying out language expressions. This study aims to describe how to design and design assessments in the psychomotor domain in learning Arabic. The method used in this research is descriptive qualitative with the type of research (library research), based on the method and type of research, the data sources are books and scientific articles that intersect with the subject matter. The results showed that the design and design of the psychomotor domain assessment instrument in Arabic learning could be done in the form of tests and non-tests. Test assessment instruments can be carried out when the learning process has taken place, and non-test instruments can be carried out during the process, namely when students practice.